Clinicopathological Characteristics of Young Patients With Pancreatic Cancer: An Analysis of Data From Pancreatic Cancer Registry of Japan Pancreas Society. Issue 10 (November 2016) - Eguchi, Hidetoshi; Yamaue, Hiroki; Unno, Michiaki; Mizuma, Masamichi; Hamada, Shin; Igarashi, Hisato; Kuroki, Tamotsu; Satoi, Sohei; Shimizu, Yasuhiro; Tani, Masaji; Tanno, Satoshi; Hirooka, Yoshiki; et al.
Abstract : Objectives: The aim of this study was to determine the characteristics of patients with pancreatic ductal adenocarcinoma younger than 40 years. Methods: Data from the Japan Pancreas Society's nationwide Pancreatic Cancer Registry were analyzed retrospectively. Clinicopathological characteristics were compared in patients who were grouped according to age, namely, younger than 40 years versus 40 years and older. Results: Of the 36 145 patients in the database, the younger group included 526 (1.5%) patients. A family history of pancreatic cancer was not more frequent in the younger group. The frequency of Union Internationale Contre le Cancer T4 and M1 were both significantly higher in younger patients, resulting in a higher percentage of patients with Union Internationale Contre le Cancer stage IV. Pancreatectomy was performed less frequently in the younger group, and R0 resection was also less frequent. The overall survival rate was significantly better in the older group, whereas in surgically resected patients, the overall survival and recurrence-free survival rates were not different between the 2 groups. Conclusions: Younger patients with pancreatic adenocarcinoma were more often diagnosed at advanced stages, and the overall survival rate was worse than that in older patients. Family genetic background and the prognoses of patients who underwent surgery were similar between the 2 groups.